Numerical Modeling in Energy and Environment - Eftekharian, Esmaeel; Ong, Robert H. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Numerical methods have become crucial in recent years and have been applied in many research fields. Among these, environmental and energy research has become increasingly relevant. This Special Issue comprises a recent advances in research relating to numerical modeling applied to energy and environment.